PENINGKATAN KOMITMEN ORGANISASI MELALUI INFORMASI ASIMETRI, KETIDAKPASTIAN LINGKUNGAN DAN PARTISIPASI PENGANGGARAN SERTA DAMPAKNYA PADA TIMBULNYA SENJANGAN ANGGARAN (Studi Empiris pada Koperasi Karta Jaya Semarang) - DHEASEY AMBONINGTYAS (Universitas Pandanaran, 2015)
With the rapid change in the era of globalization, the Cooperative of Karta Jaya Semarang should be able tocompete and stay ahead in business so the managers are able to plan the budget carefully, as a result the cooperativeactivities can be run in an integrated and focused to achieve the set goals. The underlying problem in Cooperatives ofKarta Jaya Semarang is that its budgetary slack occurred very significantly between the budget and the realization ofthe existing operational costs.The purpose of the study is to test empirically the effect of asymmetry information, uncertainty of theenvironment and budgetary participation toward the budgetary slack through the organization's commitment at theCooperative of Karta Jaya Semarang. In this study, the population is 38 functional managers who work in severalbranches in Cooperatives of Karta Jaya Semarang. Looking at the total population is only 38 respondents, so it iseligible to serve all as a sample. Consequently, this research is called census research; it is because the terms of thestudy area includes only areas or subjects that are very narrow. The statistical analysis in this study is a structuralequation modeling (SEM) and Partial Least Square method.Based on test results, it shows that asymmetry information has no effect on the organization's commitment atthe Cooperative of Karta Jaya Semarang, meaning that the high asymmetry information performed by the managers ofcooperatives showed low support of managers for organizations that does not affect the strong commitment to theorganization. Environmental uncertainty negatively affects organizational commitment, meaning that the higher themanager's inability to predict an uncertain of the environment, it suggests that managers' commitment to theorganization showed a decrease. Budgetary participation does not affect organizational commitment, which means thatthe lower the involvement of managers in the preparation of the budget, it does not affect the manager's commitment tothe organization. Organizational commitment can be an intervening variable among asymmetry information and thebudgetary slack, environmental uncertainty and the budgetary slack as well as budgetary participation and thebudgetary slack. Organizational commitment negatively affects the budgetary slack.Keywords: Asymmetry Information, environmental uncertainty and budgetary participation, organizationalcommitment and budgetary slack